The Postmodernist as Academic Leftist; or, How to Stop Worrying and Learn to Love Being Politically Correct - Eugene W. Holland (Studies in 20th & 21st Century Literature, 2014)
The Postmodernist as Academic Leftist; or, How to Stop Worrying and Learn to Love Being Politically Correct
Keywords: leftism; politcal correctness; acedemia; postmodernism